Regenerated coal flame retardant as well as preparation method and application thereof
By developing recycled coal flame retardant with a hydrotalcite-like structure, the existing flame retardant has solved the problem of poor effect and inability to regenerate in preventing coal spontaneous combustion, and achieved excellent flame retardant performance and long-term flame retardant effect.
Patent Information
- Application Number
- CN202411786112.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
Existing flame retardants are poor in preventing coal from being spontaneously ignited and cannot be regenerated, resulting in an increase in the cost of coal flame retardant.
A regenerated coal flame retardant is developed, with a chemical composition of MgAl3Six, in which 0.2≤x≤1.6. Through the co-soluble and reaction of magnesium salt, aluminum salt and silicate, a flame retardant material with a hydrotalcite-like structure is formed, and it has renewable properties through a specific preparation method.
The regenerated coal flame retardant not only has excellent flame retardant properties, but also can effectively prevent coal from being spontaneously ignited, but also regenerate damaged structures during the flame retardant process in a humid and hot environment, thereby achieving a long-term flame retardant effect.
Smart Images

Figure CN119528151A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials, and specifically relates to a regenerative coal flame retardant and a preparation method and application thereof. Background Art
[0002] With the progress of human society and the rapid development of science and technology, the demand for energy is also increasing. In the development of coal resources, its safety hazards often come from the spontaneous combustion of coal, because it is inevitable to come into contact with oxygen, and there are active substances in the coal seam that react under the action of oxygen to release a large amount of heat energy, which leads to the temperature of each layer. When the temperature rises to a certain level, it will cause the spontaneous combustion of coal, resulting in many fire hazards. It poses a great threat to the safety of life and property of miners, and coal resources will also be lost. Therefore, in order to prevent and control fire accidents caused by spontaneous combustion of coal, the most effective and safest fundamental way among many methods is to prevent the occurrence of spontaneous combustion of coal. It can be seen that the development of coal fire prevention and extinguishing materials is of great significance.
[0003] At present, different types of flame retardants have been developed, but most of these flame retardants are not renewable and cannot achieve long-term flame retardancy. They need to be replaced regularly, which increases the cost of coal flame retardancy. Therefore, it is of great significance to develop coal flame retardants with renewable properties. Summary of the invention
[0004] In view of the above-mentioned prior art, the present invention provides a regenerative coal flame retardant and a preparation method and application thereof, so as to solve the technical problems that the existing flame retardants have poor flame retardant effects and cannot be regenerated.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is to provide a regenerative coal flame retardant, the chemical composition of the regenerative coal flame retardant is MgAl3Si x , where 0.2≤x≤1.6.
[0006] Based on the above technical solution, the present invention can also be improved as follows.
[0007] Furthermore, the chemical composition of the regenerative coal flame retardant is MgAl3Si 1.6 .
[0008] The present invention also discloses a method for preparing the above-mentioned regenerative coal flame retardant, comprising the following steps:
[0009] S1: Dissolve magnesium salt and aluminum salt in water at a molar ratio of magnesium:aluminum = 3:1 to obtain solution A; dissolve silicate in water to obtain solution B; dissolve NaOH and Na2CO3 in water to obtain a mixed alkaline solution C;
[0010] S2: Heat solution A to 55-65°C, then add solution B dropwise to solution A under stirring, with the molar ratio of silicon to magnesium being 0.2-1.6:1; stir for 45-90 min; then adjust the pH of the system to 10-12 with a mixed alkaline solution C, continue stirring for 45-90 min, and obtain a crystallized system;
[0011] S3: placing the crystallization system at 60-70 °C for 90-150 min and collecting the solid product;
[0012] S4: Wash the solid product with deionized water until it is neutral, then dry it at 75-80 °C for 10-15 h, and grind it into powder.
[0013] Furthermore, the magnesium salt is MgCl2·6H2O; and the aluminum salt is AlCl3·6H2O.
[0014] Furthermore, the silicate is sodium silicate.
[0015] Furthermore, the concentration of NaOH in the mixed alkaline solution C is 2 mol / L, and the concentration of Na2CO3 is 0.5 mol / L.
[0016] Furthermore, the stirring speed in S2 is 500 rpm.
[0017] Furthermore, the particle size of the powder ground in S4 does not exceed 100 mesh.
[0018] The present invention discloses the use of the above-mentioned regenerative coal flame retardant in preventing coal spontaneous combustion. The method of preventing coal spontaneous combustion is to uniformly mix the regenerative coal flame retardant and coal in a mass ratio of 1:5.
[0019] The beneficial effects of the present invention are:
[0020] The present invention uses magnesium salt and aluminum salt as the base material, and combines with silicon in silicate to form a flame retardant material with a hydrotalcite-like structure under specific conditions. The special structure not only makes it have excellent flame retardant properties and can effectively prevent coal from spontaneous combustion, but also can regenerate the hydrotalcite structure destroyed in the flame retardant process in a hot and humid environment, thereby achieving a long-term flame retardant effect on coal. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The regenerative coal flame retardant MgAl3Si prepared by the present invention x Flame retardant effect;
[0022] Figure 2 The regenerative coal flame retardant MgAl3Si prepared by the present invention x The effect of addition amount on the flame retardant effect of coal;
[0023] Figure 3 The regenerative coal flame retardant MgAl3Si prepared by the present invention x The flame retardant effect of coal before and after use and after regeneration;
[0024] Figure 4 The regenerated coal flame retardant MgAl3Si prepared by the present invention x XRD characterization of samples before and after use and after regeneration. DETAILED DESCRIPTION
[0025] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0026] Example 1
[0027] A regenerative coal flame retardant is prepared by the following steps:
[0028] (1) Weigh 15.24 g of MgCl2·6H2O and 54.32 g of AlCl3·6H2O into a 1000 mL beaker, add 200 mL of deionized water, and stir and dissolve them in a water bath at 60 °C at 500 rpm to obtain solution A.
[0029] (2) Weigh 2.04 g of sodium silicate into a 500 mL beaker, add 100 mL of deionized water, and stir to dissolve to obtain solution B;
[0030] (3) Weigh 40 g of NaOH and 26.50 g of Na2CO3 into a 1000 mL beaker, add deionized water to 500 mL to obtain a mixed alkaline solution C of 2 mol / L NaOH and 0.5 mol / L Na2CO3;
[0031] (4) Solution A was stirred continuously at 500 rpm in a water bath at 60 °C, and then Solution B was added to a constant pressure titration funnel and slowly added dropwise to the continuously stirred Solution A at a uniform speed; after the addition was complete, the solution was continuously stirred at 500 rpm in a water bath at 60 °C for 1 h; then, the mixed alkaline solution C was titrated until the pH of the solution was 11. After the pH of the reaction solution stabilized, the water bath temperature was changed to 65 °C and stirring was continued for 1 hour to obtain a crystallized system;
[0032] (5) Take the crystallization system out of the water bath, seal it with plastic wrap, and place it in a forced air drying oven for crystallization at 65 °C for 2 hours;
[0033] (6) Take out the crystallized product, assemble the suction filtration device, and filter and wash with deionized water until the pH value of the product is 7;
[0034] (7) The product after filtration and washing is transferred to a clean beaker, placed in a forced air drying oven, the oven door is closed, the temperature of the forced air drying oven is set to 80 °C, and dried for 12 h; the dried product is ground and filtered with a 100-mesh sieve, and the resulting powder is collected to obtain a regenerated coal flame retardant with a magnesium-aluminum ratio of 1:3 and a silicon content of 20% by molar amount of magnesium, expressed as MgAl3Si 0.2 .
[0035] Example 2
[0036] A regenerative coal flame retardant is prepared by the following steps:
[0037] (1) Weigh 12.2 g of MgCl2·6H2O and 43.46 g of AlCl3·6H2O into a 1000 mL beaker, add 200 mL of deionized water, and stir and dissolve them in a water bath at 55 °C at 500 rpm to obtain solution A.
[0038] (2) Weigh 2.93 g of sodium silicate into a 500 mL beaker, add 100 mL of deionized water, and stir to dissolve to obtain solution B;
[0039] (3) Weigh 40 g of NaOH and 26.50 g of Na2CO3 into a 1000 mL beaker, add deionized water to 500 mL to obtain a mixed alkaline solution C of 2 mol / L NaOH and 0.5 mol / L Na2CO3;
[0040] (4) Solution A was continuously stirred at 500 rpm in a water bath at 55°C, and then Solution B was added to a constant pressure titration funnel and slowly added dropwise to the continuously stirred Solution A at a uniform speed; after the addition was complete, the solution was continuously stirred at 500 rpm in a water bath at 55°C for 90 min; then, the mixed alkaline solution C was titrated until the pH of the solution was 12. After the pH of the reaction solution was stable, the water bath temperature was changed to 60°C and stirring was continued for 90 min to obtain a crystallized system;
[0041] (5) Take the crystallization system out of the water bath, seal it with plastic wrap, and place it in a forced air drying oven for crystallization at 60 °C for 150 min;
[0042] (6) Take out the crystallized product, assemble the suction filtration device, and filter and wash with deionized water until the pH value of the product is 7;
[0043] (7) The product after filtration and washing is transferred to a clean beaker, placed in a forced air drying oven, the oven door is closed, the temperature of the forced air drying oven is set to 75 °C, and dried for 15 h; the dried product is ground and filtered with a 100-mesh sieve, and the resulting powder is collected to obtain a regenerated coal flame retardant with a magnesium-aluminum ratio of 1:3 and a silicon content of 40% of the magnesium molar amount, expressed as MgAl3Si 0.4 .
[0044] Example 3
[0045] A regenerative coal flame retardant is prepared by the following steps:
[0046] (1) Weigh 16.26 g of MgCl2·6H2O and 57.94 g of AlCl3·6H2O into a 1000 mL beaker, add 200 mL of deionized water, and stir and dissolve them in a water bath at 65 °C at 500 rpm to obtain solution A.
[0047] (2) Weigh 7.81 g of sodium silicate into a 500 mL beaker, add 100 mL of deionized water, and stir to dissolve to obtain solution B;
[0048] (3) Weigh 40 g of NaOH and 26.50 g of Na2CO3 into a 1000 mL beaker, add deionized water to 500 mL to obtain a mixed alkaline solution C of 2 mol / L NaOH and 0.5 mol / L Na2CO3;
[0049] (4) Solution A was stirred continuously at 500 rpm in a water bath at 65°C, and then Solution B was added to a constant pressure titration funnel and slowly added dropwise to the continuously stirred Solution A at a uniform speed; after the addition was complete, the solution was stirred continuously at 500 rpm in a water bath at 65°C for 45 min; then, the mixed alkaline solution C was titrated until the pH of the solution was 10. After the pH of the reaction solution was stable, the water bath temperature was changed to 70°C and stirring was continued for 45 min to obtain a crystallized system;
[0050] (5) The crystallization system was taken out from the water bath, sealed with plastic wrap, and placed in a forced air drying oven for crystallization at 70 °C for 90 min.
[0051] (6) Take out the crystallized product, assemble the suction filtration device, and filter and wash with deionized water until the pH value of the product is 7;
[0052] (7) The product after filtration and washing is transferred to a clean beaker, placed in a forced air drying oven, the oven door is closed, the temperature of the forced air drying oven is set to 85 °C, and dried for 10 h; the dried product is ground and filtered with a 100-mesh sieve, and the resulting powder is collected to obtain a regenerated coal flame retardant with a magnesium-aluminum ratio of 1:3 and a silicon content of 80% of the magnesium molar amount, expressed as MgAl3Si 0.8 .
[0053] Example 4
[0054] A regenerative coal flame retardant is prepared by the following steps:
[0055] (1) Weigh 14.23 g of MgCl2·6H2O and 50.70 g of AlCl3·6H2O into a 1000 mL beaker, add 200 mL of deionized water, and stir and dissolve them in a water bath at 60 °C at 500 rpm to obtain solution A.
[0056] (2) Weigh 13.67 g of sodium silicate into a 500 mL beaker, add 100 mL of deionized water, and stir to dissolve to obtain solution B;
[0057] (3) Weigh 40 g of NaOH and 26.50 g of Na2CO3 into a 1000 mL beaker, add deionized water to 500 mL to obtain a mixed alkaline solution C of 2 mol / L NaOH and 0.5 mol / L Na2CO3;
[0058] (4) Solution A was stirred continuously at 500 rpm in a water bath at 60 °C, and then Solution B was added to a constant pressure titration funnel and slowly added dropwise to the continuously stirred Solution A at a uniform speed; after the addition was complete, the solution was continuously stirred at 500 rpm in a water bath at 60 °C for 1 h; then, the mixed alkaline solution C was titrated until the pH of the solution was 11. After the pH of the reaction solution stabilized, the water bath temperature was changed to 65 °C and stirring was continued for 1 hour to obtain a crystallized system;
[0059] (5) Take the crystallization system out of the water bath, seal it with plastic wrap, and place it in a forced air drying oven for crystallization at 65 °C for 2 hours;
[0060] (6) Take out the crystallized product, assemble the suction filtration device, and filter and wash with deionized water until the pH value of the product is 7;
[0061] (7) The product after filtration and washing is transferred to a clean beaker, placed in a forced air drying oven, the oven door is closed, the temperature of the forced air drying oven is set to 80 °C, and dried for 12 h; the dried product is ground and filtered with a 100-mesh sieve, and the resulting powder is collected to obtain a regenerated coal flame retardant with a magnesium-aluminum ratio of 1:3 and a silicon content of 160% of the magnesium molar amount, expressed as MgAl3Si 1.6 .
[0062] Experimental Example 1
[0063] The regenerated coal flame retardant prepared in the above-mentioned embodiments was tested for its inhibitory performance. The specific test method is as follows: different types of regenerated coal flame retardants were evenly mixed with carbon powder at a mass ratio of 1:5, and the mixture was placed in a quartz reaction tube. Under air flow conditions (flow rate of 40 mL / min), the temperature was heated from room temperature to 300°C, and the heating rate was 5°C / min. The gas produced during the thermal decomposition of the coal was collected with a gas collecting bag at the initial (room temperature), 50°C, 100°C, 150°C, 180°C, 190°C, 200°C, 235°C, 270°C and 300°C, and the collection time was 1 minute. The collected gas was analyzed by a gas chromatograph, and the data of the amount of CO produced as the temperature increased was recorded, thereby characterizing the change in the thermal decomposition temperature of the coal after the addition of the inhibitor. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared regenerated coal flame retardants with different Si contents all have good coal flame retardant properties, and when the magnesium-aluminum ratio is 1:3 and the Si introduction amount is 160% of the amount of Mg substance (MgAl3Si 1.6 ) exhibits the best coal flame retardant performance.
[0064] Experimental Example 2
[0065] According to the experimental example, MgAl3Si 1.6 For the best flame retardant, optimize the amount of flame retardant added:
[0066] (1) Weigh 0.9 g MgAl3Si 1.6 The powder was evenly mixed with 2.7 g of carbon powder (flame retardant: carbon powder = 1:3), and the evenly mixed powder was transferred to a quartz tube reactor containing quartz wool, and the quartz tube was installed in an electric heating furnace; the gas tank switch was turned on, the flow meter was set to 40 mL / min, and air was passed for 10 min.
[0067] (2) Set the electric heating furnace program, the heating rate is 5 ℃ / min, and the flow meter flow rate is kept at 40 mL / min; first increase the temperature from room temperature to 50 ℃, keep it for 2 min, and then increase it to 300 ℃. Use a gas collection bag to collect the generated gas at the initial (room temperature), 50 ℃, 100 ℃, 150 ℃, 180 ℃, 190 ℃, 200 ℃, 235 ℃, 270 ℃ and 300 ℃. The collection time is 1 minute, and a total of 10 samples are collected.
[0068] (3) In order of increasing temperature, use a syringe to take out 1 mL of the gas collected in the gas collection bag and inject it into the gas chromatograph for analysis.
[0069] (4) The flame retardant effect of the flame retardant: carbon powder ratio of 1:5, 1:7 and 1:9 was tested in the same way (the total mass of hydrotalcite and carbon powder was kept at 3.6 g). Only the ratio of hydrotalcite to carbon powder was changed, and other conditions remained the same. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that when the total mass is constant, the flame retardant (MgAl3Si 1.6 ) the more it produces, the less CO gas it produces, that is, the higher the flame retardancy. 1.6 The flame retardant effect increases with the increase in the amount of flame retardant material used, especially when the ratio increases from 1:7 to 1:5, the flame retardant effect increases the most. When it continues to increase to 1:3, the flame retardant effect does not increase much. Therefore, MgAl3Si 1.6 The flame retardant effect and economic benefits are best when the mass ratio of flame retardant material to coal is 1:5.
[0070] Experimental Example 3
[0071] In order to conduct the recovery experiment, the regenerated coal flame retardant is firstly made into the state after use, and then the recovery experiment is conducted on it. The specific steps are as follows:
[0072] (1) Weigh 4 g MgAl3Si using an electronic analytical balance 1.6 The powder was placed in a quartz tube reactor with quartz wool, and the quartz tube was installed in an electric heating furnace; the gas tank switch was turned on, the flow meter was set to 40 mL / min, and air was passed for 10 minutes.
[0073] (2) Set the electric heating furnace program, with a heating rate of 5 °C / min and a flow rate of 40 mL / min; first raise the temperature from room temperature to 50 °C, maintain for 2 min, and then raise the temperature to 300 °C.
[0074] (3) When the temperature drops to room temperature, take out the used recycled coal flame retardant powder and divide it into two equal parts, which are recorded as sample ① and sample ②.
[0075] (4) Re-immersion recovery experiment: transfer sample ② into a clean beaker, add a certain amount of deionized water to completely immerse sample ②, and soak it at room temperature for ten days; after soaking, filter out the water and dry it in a forced air drying oven at 60°C for 12 hours to obtain a re-recoverable flame retardant material.
[0076] (5) The retardant properties of the unrecovered sample (sample ①) and the recovered flame retardant material were tested according to the retardant properties test method in Experimental Example 2. The results are as follows: Figure 3 As shown; and tested the original flame retardant material (MgAl3Si 1.6 ), unrecovered sample (sample ①), and recovered flame retardant material. The results are as follows Figure 4 shown.
[0077] from Figure 3 and Figure 4 It can be seen that compared with the new flame retardant, the used flame retardant no longer has good coal flame retardant performance, and after the used flame retardant material is treated in a humid environment, its flame retardant performance is greatly restored. It can be seen that the regenerated coal flame retardant prepared by the present invention has good regeneration performance in a humid environment and can achieve a long-term flame retardant effect.
[0078] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A regenerative coal flame retardant, characterized in that: The chemical composition of the regenerative coal flame retardant is MgAl3Si x , where 0.2≤x≤1.
6.
2. The regenerative coal flame retardant according to claim 1, characterized in that: The chemical composition of the regenerative coal flame retardant is MgAl3Si 1.6 .
3. The method for preparing the regenerative coal flame retardant according to claim 1 or 2, characterized in that: The following steps are involved: S1: Dissolve magnesium salt and aluminum salt in water at a molar ratio of magnesium:aluminum = 3:1 to obtain solution A; dissolve silicate in water to obtain solution B; dissolve NaOH and Na2CO3 in water to obtain a mixed alkaline solution C; S2: Heat solution A to 55-65°C, then add solution B dropwise to solution A under stirring, wherein the molar ratio of silicon to magnesium is 0.2-1.6:1; The mixture was stirred at this temperature for another 45 to 90 minutes; the pH of the system was then adjusted to 10 to 12 with a mixed alkaline solution C, and the mixture was stirred at this temperature for another 45 to 90 minutes to obtain a crystallized system; S3: placing the crystallization system at 60-70 °C for 90-150 min and collecting the solid product; S4: Wash the solid product with deionized water until it is neutral, then dry it at 75-80 °C for 10-15 h, and grind it into powder.
4. The preparation method according to claim 3, characterized in that: The magnesium salt is MgCl2·6H2O; the aluminum salt is AlCl3·6H2O.
5. The preparation method according to claim 3, characterized in that: The silicate is sodium silicate.
6. The preparation method according to claim 3, characterized in that: The concentration of NaOH in the mixed alkaline solution C is 2 mol / L, and the concentration of Na2CO3 is 0.5 mol / L.
7. The preparation method according to claim 3, characterized in that: The stirring speed in S2 is 500 rpm.
8. The preparation method according to claim 3, characterized in that: The particle size of the powder ground in S4 does not exceed 100 mesh.
9. Use of the regenerative coal flame retardant according to claim 1 or 2 in preventing coal spontaneous combustion.
10. The use according to claim 9, characterized in that: Mix the regenerated coal flame retardant and coal in a mass ratio of 1:5.